Fibrin Gel Network Characteristics and Coronary Heart Disease: Relations to Plasma Fibrinogen Concentration, Acute Phase Protein, Serum Lipoproteins and Coronary Atherosclerosis - Fatah, Kamaran; Hamsten, Anders; Blombäck, Birger; Blombäck, Margareta (Thrombosis and Haemostasis, 1992)
The native fibrin gel structure formed in vitro from plasma samples was examined by liquid permeation of the hydrated fibrin gel networks in 18 men who had suffered a myocardial infarction before the age of 45 years and in 20 control subjects. Patients with an elevated plasma fibrinogen concentration had a considerably lower fibrin gel porosity (permeability coefficient, Ks) compared with patients with a normal plasma fibrinogen level and with controls. The calculated fiber mass-length ratio of the fibrin gel networks was decreased in both patient groups. Gel porosity differed markedly between individuals at a given plasma fibrinogen concentration. Fairly strong inverse correlations were found between plasma orosomucoid level on the one hand and Ks (r = –0.617, p <0.01) or fiber mass-length ratio (r = –0.499, p <0.05) on the other. The low density lipoprotein (LDL) cholesterol concentration also correlated inversely with Ks (r = –0.471, p <0.05) and fiber mass-length ratio (r = –.522, p <0.05). Significant inverse relations, which were independent of plasma fibrinogen and lipoprotein concentrations, were detected between Ks (r = –.519, p <0.05) and calculated fiber mass-length ratio (r = –.723, p <0.001) and number and severity of coronary artery stenoses determined by angiography. A proneness to formation of tight, rigid and space-filling fibrin network structures with small pores thus appears to be associated with premature coronary artery disease.